P300 event-related potentials in patients with different subtypes of depressive disorders - Wang, Yun; Li, Canxin; Liu, Xiaohua; Peng, Daihui; Wu, Yan; Fang, Yiru (Frontiers in Psychiatry, 2023)
Objective To explore the differences in event-related potentials (ERPs) of the subclinical types of major depressive disorders (MDD): melancholic (MEL), atypical (ATY), and anxious (ANX). Methods Patients with MDD treated in the Clinical Department of Shanghai Mental Health Center between September 2017 and December 2020 were prospectively included. This study was approved by the Ethics Committee of the Shanghai Mental Health Center. They were evaluated using the Mini-International Neuropsychiatric Interview (MINI), 17-item Hamilton Depression Scale (HAMD-17), 30-item Self-rated Inventory of Depressive Symptomatology (IDS-30SR), 16-item Quick Inventory of Negative Symptom Scale (QIDS-16SR), and auditory and visual P300 ERPs. Results Finally, 27, 14, and 20 patients with MEL, ATY, and ANX MDD were included in this study, respectively. There were no significant differences in demographic characteristics and HAMD-17, IDS-30SR, and QIDS-16SR total scores among the three groups (all P > 0.05). On the C3 lead, the latency for patients with MEL MDD was the longest, and the latency for patients with ATY MDD was the shortest (MEL vs. ATY vs. ANX: 373.89 ± 6.60 vs. 344.79 ± 9.78 vs. 359.33 ± 7.62, P = 0.039). On the Pz lead, the latency for patients with MEL MDD was the longest, and the latency for patients with ATY MDD was the shortest (MEL vs. ATY vs. ANX: 376.14 ± 6.51 vs. 347.21 ± 9.42 vs. 362.22 ± 8.63, P = 0.047). There were no differences in visual P300 ERPs among the three groups. Conclusion There are significant differences in auditory C3 and Pz latency among MEL, ATY, and ANX MDD. These differences could help diagnose the subtype of MDD.